Diffusion of aniline blue injected into the thyroarytenoid muscle as a proxy for botulinum toxin injection: an experimental study in cadaver larynges - Alonso, Valéria Maria de Oliveira; Chagury, Azis Arruda; Hachiya, Adriana; Imamura, Rui; Tsuji, Domingos Hiroshi; Sennes, Luiz Ubirajara (International Archives of Otorhinolaryngology, 2013)
Introduction: Endolaryngeal injection of botulinum toxin into the thyroarytenoid (TA) muscle is one of the methods for treatment of focal laryngeal dystonia. However, after treatment, there is variation in laryngeal configuration as well as the side effects reported by patients. As a consequence of the functional variability of results, it was hypothesized that botulinum toxin diffuses beyond the limits of the muscle into which it is injected.Objectives: After injection of botulinum toxin into the TA muscle for the treatment of focal laryngeal dystonia, patients differ in terms of laryngeal configuration and side effects. We hypothesized that this toxin diffuses from the target muscle to adjacent muscles.Method: The TA muscles of 18 cadaver larynges were injected with aniline blue (0.2 mL). After fixation in formaldehyde and nitric acid decalcification, the larynges were sectioned in the coronal plane and the intrinsic muscles were analyzed.Results: We found diffusion of aniline blue to the lateral cricoarytenoid muscle, cricothyroid muscle, and posterior cricoarytenoid muscle in 94.3%, 42.9%, and 8.6% of the cases, respectively. In terms of the degree of diffusion to adjacent muscles, we found no differences related to the size (height and width) of the TA muscle or to gender.Conclusions: Our findings suggest that diffusion of botulinum toxin from its injection site in the TA muscle to the lateral cricoarytenoid muscle is likely in most cases. On the other hand, diffusion to the cricothyroid muscle occurs in approximately half of cases and diffusion to the posterior cricoarytenoid muscle occurs in very few cases.
Keywords: Larynx; Dysphonia; Botulinum Toxins; Diffusion; Biological Transport